Alarmin-activated B cells accelerate murine atherosclerosis after myocardial infarction via plasma cell-immunoglobulin-dependent mechanisms. (18th December 2020) - Kyaw, Tin; Loveland, Paula; Kanellakis, Peter; Cao, Anh; Kallies, Axel; Huang, Alex L; Peter, Karlheinz; Toh, Ban-Hock; Bobik, Alex
Abstract: Aims : Myocardial infarction (MI) accelerates atherosclerosis and greatly increases the risk of recurrent cardiovascular events for many years, in particular, strokes and MIs. Because B cell-derived autoantibodies produced in response to MI also persist for years, we investigated the role of B cells in adaptive immune responses to MI. Methods and results : We used an apolipoprotein-E-deficient (ApoE −/− ) mouse model of MI-accelerated atherosclerosis to assess the importance of B cells. One week after inducing MI in atherosclerotic mice, we depleted B cells using an anti-CD20 antibody. This treatment prevented subsequent immunoglobulin G accumulation in plaques and MI-induced accelerated atherosclerosis. In gain of function experiments, we purified spleen B cells from mice 1 week after inducing MI and transferred these cells into atherosclerotic ApoE −/− mice, which greatly increased immunoglobulin G (IgG) accumulation in plaque and accelerated atherosclerosis. These B cells expressed many cytokines that promote humoural immunity and in addition, they formed germinal centres within the spleen where they differentiated into antibody-producing plasma cells. Specifically deleting Blimp-1 in B cells, the transcriptional regulator that drives their terminal differentiation into antibody-producing plasma cells prevented MI-accelerated atherosclerosis. Alarmins released from infarcted hearts were responsible for activating B cells via toll-like receptors and deleting MyD88, the canonical adaptor protein for inflammatory signalling downstream of toll-like receptors, prevented B-cell activation and MI-accelerated atherosclerosis. Conclusion : Our data implicate early B-cell activation and autoantibodies as a central cause for accelerated atherosclerosis post-MI and identifies novel therapeutic strategies towards preventing recurrent cardiovascular events such as MI and stroke. Graphical Abstract: